Penanaman Pohon untuk Mengembalikan Fungsi Pargodungan Atau Kompleks Gereja di HKBP Lumban Hariara Sitoluama Laguboti Kabupaten Toba - Pahala Jannen Simanjuntak; Leonardo Simanjuntak; Febryandi Pardede; Eva Sihotang; Reza Lumban Batu; Rudi Siahaan; Irena Claudia Simanjuntak (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2026)
The church is not only seen from its large and beautiful building standing in a place. But in addition to the building, it is also necessary to pay attention to the complex or pargodungan which has a dual and vital function to the residents and surroundings. Since the missionaries, they have made the church complex a shady place and a pilot center for the wider community. Namely by planting trees that can be enjoyed by the congregation and the community as well. So in restoring the function of the church complex as done by the missionaries in the past, it is necessary to recognize the planting of trees in the church complex with various types of plants. So that the dual function of the church complex receives attention among the congregation. Where the church complex is a gathering place with a variety of activities for congregation members ranging from Sunday School children to the elderly. Both functions are that the church complex becomes the lungs around the church in terms of producing fresh air, shelter and preserving the environment.